7 - A qualitative application of Amartya Sen’s ‘development as freedom’ theory to an understanding of social grants in South Africa. - Mzingaye Brilliant Xaba (African Sociological Review, 2016)
Amartya Sen argued that poverty is the “deprivation” of a person’s capability to lead a “good life”, therefore ending poverty means meeting basic physical and social needs, and enabling meaningful economic and political choices. The aim of this paper is to investigate whether and how social grants enable “choices” in Sen’s sense. In-depth interviews conducted with social grants recipients’ in this study provided evidence that social grants reduce poverty, both in terms of helping grants recipients to meet basic needs, and enabling them to make more choices, such as buying food, accessing education and health care, as well as facilitating job searches and starting small businesses. However, there was also evidence that showed that grants are inadequate to entirely remove the “unfreedoms” facing the poor because the grants are too small to adequately cover basic needs in the context of large family sizes, a serious and long-term lack of resources, persistent unemployment, and high indebtedness. Further, these grants could enable only a limited expansion of “choices”. This paper argues that social grants in South Africa do enable recipients some “choices” although access to these “choices” is limited. It is envisaged that this paper will help academics to think more about the extent of the developmental impact of social grants in South Africa.